Walking speed at the acute and subacute stroke stage: A descriptive meta-analysis - Tasseel-Ponche, Sophie; Delafontaine, Arnaud; Godefroy, Olivier; Yelnik, Alain P.; Doutrellot, Pierre-Louis; Duchossoy, Charline; Hyra, Marie; Sader, Thibaud; Diouf, Momar (Frontiers in Neurology, 2022)
Gait disorders are one of the leading patient complaints at the sub-acute stroke stage (SSS) and a main determinant of disability. Walking speed (WS) is a major vital and functional index, and the Ten-Meter Walk Test is considered the gold standard after stroke. Based on a systematic review of the literature, studies published between January 2000 and November 2021 were selected when WS was reported (ten-meter walk test for short distance and/or 6-min walking distance for long distance) within 6 months following a first ischemic and/or hemorrhagic stroke (SSS) in adults prior to receiving specific walking rehabilitation. Following PRISMA guidelines, a meta-analysis was conducted on two kinds of WS: the principal criterion focused on short-distance WS (ten-meter walking test) and the secondary criteria focused on long-distance WS (6-min test) and meta-regressions to study the association of WS with balance, cognitive disorders and autonomy. Nine studies comprising a total of 939 data on post-stroke patients were selected. The weighted average age was 61 years [95% IC [55-67] and males represented 62% ± 2.7 of patients [57-67]. Average short-distance WS was 0.36 ± 0.06 m.s−1 [95% CI (0.23–0.49)]. Average long-distance WS was 0.46 ± 0.1 m.s−1 [95% CI (0.26–0.66)]. The funnel plot revealed asymmetry of publication bias and high heterogeneity of the nine studies (I2 index 98.7% and Q-test p < 0.0001). Meta-regressions of secondary endpoints could not be performed due to a lack of study data. At the SSS, WS would be lower than data in general population published in literature, but above all, lower than the WS required for safe daily autonomy and community ambulation after stroke. WS must be a priority objective of stroke rehabilitation to increase walking function but also for survival, autonomy, social participation and health-related quality of life.